2015
DOI: 10.35838/jrap.2015.002.02.20
|View full text |Cite
|
Sign up to set email alerts
|

Reaksi Pasar Dalam Bentuk Return Sebelum, Selama, dan Sesudah Peristiwa Piala Dunia Tahun 2014 pada Pasar Modal Asean

Abstract: A B S T R A C T Investor realized that the stock market gradually decreased during World Cup.The research aimed to analyze the return of market reaction which happenned before, during, and after World Cup 2014 on ASEAN stock market. The sample involved 181 companies were included in LQ-45, STI, FTSE BM KLCI, SET 50, PSEI index, which fulfilled the reseach criteria. The data analysis technique used was one sampel t-test with quantitative data. Based on the result, can be concluded that Indonesia and Thail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…In the opposite occurred in Athen when there was a cancellation the venue as a host in 1996. Indonesia and Thailand were also very reacting to the world cup event 2014, so that can be concluded that at that time non economic event or event such as sport can give the impact to stock return (Pratiwi & Yusuf, 2015). According to the background and the previous research so the hypothesis in this research is H1 = occurring the significant abnormal return on the phenomena of Asian Games 2018 H2 = there is the significant different abnormal return in after or before in Asian Games 2018.…”
Section: Literatur Reviewmentioning
confidence: 85%
See 3 more Smart Citations
“…In the opposite occurred in Athen when there was a cancellation the venue as a host in 1996. Indonesia and Thailand were also very reacting to the world cup event 2014, so that can be concluded that at that time non economic event or event such as sport can give the impact to stock return (Pratiwi & Yusuf, 2015). According to the background and the previous research so the hypothesis in this research is H1 = occurring the significant abnormal return on the phenomena of Asian Games 2018 H2 = there is the significant different abnormal return in after or before in Asian Games 2018.…”
Section: Literatur Reviewmentioning
confidence: 85%
“…The research use 181 sample of the company includes in ASEAN capital market. The technique of the research conducted with analyze statistics one sample t-test with quantitative data (Pratiwi & Yusuf, 2015). On the five ASEAN countries that be observed, for 24 days observation with significant value 5% and 10%.…”
Section: Literatur Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…(Costa & Sukartha, 2020) conducted research on a comparison of market reactions in the US, China and Indonesia to the US-China Trade War negotiations, with the results of the study namely that there were differences in reactions between the American, Chinese and Indonesian stock markets to the announcement of the results of the US trade war negotiations -China. (Pratiwi & Yusuf, 2015) conducted research on capital market reactions before, during and after the 2014 world cup events on the ASEAN capital market, resulting that the Indonesian and Thai capital markets strongly reacted to the 2014 world cup events.…”
Section: Introductionmentioning
confidence: 99%